Chitosan based supramolecular polypseudorotaxane as a pH-responsive polymer and their hybridization with mesoporous silica-coated magnetic graphene oxide for triggered anticancer drug delivery. (12th October 2015) - Pourjavadi, Ali; Mazaheri Tehrani, Zahra; Jokar, Safura
Abstract: Chitosan based polyseudorotaxane was designed as a pH-responsive supramolecular polymeric shell around the mesoporous silica-coated magnetic graphene oxide (Fe3 O4 @GO@mSiO2 ). It was used for doxorubicin delivery at cancerous tissue in a controlled manner. The core-shell nanocarrier was formed due to electrostatic interaction between chitosan and carboxylated surface of Fe3 O4 @GO@mSiO2 . The maximum release occurred at pH 5.5 (pH of endosomes) because the shell collapsed at this pH. The drug nanocarrier has potential application in tumor therapy due to good pH-sensitive behavior, improved solubility and high colloidal stability in biological media. Graphical abstract: Highlights: Using hybrid nanoparticle with high loading ability and enhanced hydrophilicity. Using pH sensitive polymer shell with supramolecular polypseudorotaxane structure. Preparation of drug nanocarrier with potential application in tumor therapy.